Analisis Saluran Pemasaran Kentang Terhadap Kondisi Pasar yang Mempengaruhi Pendapatan Petani - Maulania Rahma Azzahra; Nurul Nur Fadillah; Hasna Nabila Putri; Wien Kuntari (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
Horticultural agriculture, particularly in potato production, is an important sector in maintaining food security and community welfare. However, challenges in potato marketing, such as the length of distribution chains and price fluctuations, can reduce farmers' income. This study analyzes literature related to potato marketing channels and market conditions to understand their impact on farmers' income. Through a descriptive method, data were collected from national and international journals, with a focus on production factors, marketing, and market conditions. The results show that farmers' income is influenced by the marketing channels used and market conditions such as price fluctuations. The variation in income between regions indicates the importance of further research to develop solutions that can enhance stability and potato farmers' income overall.Keywords: Potato marketing channels; potato market conditions; potato farmers' income